The Tigras Brigade of Lithuanian Partisans: its Subordination, Organisational Structure and Area of Control - Gečiauskas, Geistautas (Genocidas ir rezistencija, 2006)
In July 1999, during the construction of a road in the Adutiškis forests (Švenčionys region), a bulldozer brushed against au aluminium container full of Lithuanian partisans’ documents. For the most part, they contained the Tigras [Tiger] Brigade’s commanders’ orders, partisans’ reports, lists of partisans and correspondence documents. In 2000, these documents were hauded over to the Special Archive of Lithuania. Based on the Tigras Brigade’s archives, as well as on the records of the former KGB Archives of the Lithuanian SSR, and concentrating on the development of both the area of control and organisational structure of the Tigras Brigade, this study analyses the beginning of partisan movement in the Švenčionys area, the formation of the Tigras Brigade, the changes in the chain of command within the brigade and its subunits, exposes the tactics of the Brigade and reveals the role of the Brigade within the Lithuanian partisan movement. The latter was organised in July 1944 when the second Soviet occupation began. The initiator of the anti-Soviet resistance was the Freedom Army of Lithuania (LLA), founded as an anti-Nazi underground organisation at the end of 1941. In the former Švenčionys district. i.e. in the easternmost part of the present Republic of Lithuania, the first LLA groups were formed in 1942, and the majority of the partisans of the LLA in the Švenčionys area were based in forests in summer 1944. Since its foundation on 22 October 1944 until May 1945, the Tigras Brigade operated in Švenčionys (with the exception of the linguistically Polish Pabradė parish), Utena (with the exception of its southern part), Ukmergė (only in its Balninkai and Želva parishes), and Zarasai (only in its southern part) districts, as well as in the Vidžiai region and in the parts of Breslauja, Pastovys and Svieriai regions of the Byelorussian SSR (in the middle of the 20th century the majority of the population in these areas of the BSSR still spoke or at least were able to comprehend the Lithuanian language). On May 23, 1945, a separate partisan brigade in the Utena district was founded. Since the summer of 1945, the Tigras Brigade’s area of control extended over the Švenčionys district, as well as over the Zarasai district in the parish of Rimšė and over the aforementioned parts of the BSSR. Since the summer of 1946, the Brigade operated only in the territory that had been occupied by Poland in the years 1919?–1939. During the years 1946 to 1950, the western boundary line of the Brigade’s area of control went along the Vilnius-Daugavpils railway, the northern one extended across the Dūkštas forests, the eastern one, across the Belmontas and the Varapajevas forests (BSSR), and the southern in the Geledne forests. The commanders of the Brigade tried to expand its activity as far eastwards as they could. In this way, they hoped to ensure the integration of a future independent Lithuania with the area that Soviet Russia had acknowledged as the territory belonging to the Republic of Lithuania in the Treaty of Moscow in July 1920. After the foundation of the Tigras Brigade, it first belonged to the Vilnius Command of the LLA. In 1944, about 600 fighters were admitted to the Brigade, and by March 1945, it already had around 700 armed members. Since its foundation, the Tigras Brigade was divided into the headquarters’ squad and into companies, while the latter were made of platoons; during the years 1946 to 1950, the Brigade comprised from 8 to 4 companies. The commanders of the companies were subject to both the commander and the headquarters of the Brigade. When in January 1945 Soviet security forces destroyed the headquarters of the Vilnius Command of the LLA, the headquarters of the Tigras Brigade also performed the functions of command headquarters for several mouths. In August 1945, the Vytautas Command of the LLA was founded, which comprised several districts of northeastern Lithuania. However, in 1945, the Tigras Brigade (about 300 fighters) belonged to this Command only for two or three weeks because in September 1945 it joined the Fifth Region of the Vilnius Command of the LLA, which later became the "Greater Combat Command of the LLA" (its units operated mainly westwards from Vilnius). The period between the autumn of 1945 and the spring of 1946 was the most active time for the Brigade. Special importance should be given to the Vilnius situation at that time: if a war between the Western countries and the USSR had broken out at the time, the partisans of the same command from three directions could have attacked the capital of Lithuania. In 1946, the process of disintegration of the Brigade began: in June, based on two companies, the so-called Eastern group of the LLA was formed; at first, it united some 75 partisans and operated mainly in the Belmontas and Adutiškis forests. When in September 1946 the Tigras Brigade (some 170 fighters) returned to the Vytautas Command, the MGB took much stronger action against the Brigade. In March 1947, the Brigade (without the "Eastern group", it rejoined the Tigras Brigade only in August 1948) involved some 120 partisans, whereas in autumn of the same year, there were only some 70 fighters left. Since September 1947, the Brigade was called the Tigras Brigade of the Vytautas Command of the Area of North-Eastern Lithuania of the BDPS (United Democratic Resistance Movement), since May 1948, the Tigras Brigade of the Vytautas Command of the Area of North-Eastern Lithuania (since November 1948, of Eastern Lithuania) of the LP (Lithuanian Partisans) (since February 1949, of the LLKS [Movement of the Lithuanian Struggle for Freedom]). By September 1948, there still were as many as 50, but in January 1952, only some 20 fighters in the whole Brigade. Soviet security services with the assistance of agents among the fighters finally destroyed the Tigras Brigade in June 1952.